Multimorbidity: Constellations of Conditions across Subgroups of Midlife and Older Individuals, and Related Medicare Expenditures. Issue 1 (2017) - Koroukian, Siran M.; Schiltz, Nicholas K.; Warner, David F.; Sun, Jiayang; Stange, Kurt C.; Given, Charles W.; Dor, Avi
Introduction: The Department of Health and Human Services' 2010 Strategic Framework on Multiple Chronic Conditions called for the identification of common constellations of conditions in older adults. Objectives: To analyze patterns of conditions constituting multimorbidity (CCMM) and expenditures in a US representative sample of midlife and older adults (50–64 and ≥65 years of age, respectively). Design: A cross-sectional study of the 2010 Health and Retirement Study (HRS; n =17, 912). The following measures were used: (1) count and combinations of CCMM, including (i) chronic conditions (hypertension, arthritis, heart disease, lung disease, stroke, diabetes, cancer, and psychiatric conditions), (ii) functional limitations (upper body limitations, lower body limitations, strength limitations, limitations in activities of daily living, and limitations in instrumental activities of daily living), and (iii) geriatric syndromes (cognitive impairment, depressive symptoms, incontinence, visual impairment, hearing impairment, severe pain, and dizziness); and (2) annualized 2011 Medicare expenditures for HRS participants who were Medicare fee-for-service beneficiaries ( n =5, 677). Medicaid beneficiaries were also identified based on their self-reported insurance status. Results: No large representations of participants within specific CCMM categories were observed; however, functional limitations and geriatric syndromes were prominently present with higher CCMM counts. Among fee-for-service Medicare beneficiaries aged 50–64 years, 26.7% of the participants presented with ≥10 CCMM, but incurred 48% of the expenditure. In those aged ≥65 years, these percentages were 16.9% and 34.4%, respectively. Conclusion: Functional limitations and geriatric syndromes considerably add to the MM burden in midlife and older adults. This burden is much higher than previously reported.